2014
DOI: 10.1016/j.mjafi.2013.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Safety and effectiveness of bubble continuous positive airway pressure in preterm neonates with respiratory distress

Abstract: Bubble Continuous Positive Airway Pressure is safe, efficacious and easy to use in preterm neonates with mild to moderate respiratory distress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…The Australian study had a larger sample size than our study and also recruited extreme low birth weight babies who might not have tolerated the bCPAP machine. Similar findings were reported by Mathai et al where 2 of the 3 babies with body weight less than 1kg failed bCPAP [22]. The starting bCPAP PEEP in both studies was 6cm of water which was similar to our study.…”
Section: Plos Onesupporting
confidence: 92%
“…The Australian study had a larger sample size than our study and also recruited extreme low birth weight babies who might not have tolerated the bCPAP machine. Similar findings were reported by Mathai et al where 2 of the 3 babies with body weight less than 1kg failed bCPAP [22]. The starting bCPAP PEEP in both studies was 6cm of water which was similar to our study.…”
Section: Plos Onesupporting
confidence: 92%
“…Failure of bCPAP can include death, pneumothorax, severe intraventricular hemorrhage and bronchopulmonary dysplasia. This study was not able to provide data regarding the risk factors, however previous studies have identified the FiO 2 , lower antenatal steroid exposure, birthweight, gestational age, apnoea, late initiation of CPAP, as significant predictors of CPAP failure [24–26]. These factors and indicators of failure need to be considered in future prospective studies of bCPAP.…”
Section: Discussionmentioning
confidence: 88%
“…In a large neonatal unit in Nicaragua, a new strategy to promote the systematic use of bCPAP significantly reduced the rate of intubation and mortality [23]. A small prospective observational study from India, that was able to monitor the safety of bCPAP with pulse oximetry, radiologically and with blood gases, found bCPAP to be safe [26].…”
Section: Discussionmentioning
confidence: 99%
“…This finding was also strongly supported by the study done by Mathai SS et al, in which B-CPAP use within 24 hrs had less duration of B-CPAP (44.93±24.56 hrs) required as compared to after 24 hrs (85.57±54.16 hrs). 17 This study described the commonest cause of respiratory distress requiring B-CPAP was congenital pneumonia (23%) followed by MAS (19%), birth asphyxia (13%) and HMD (11%). Mathur NB et al postulated congenital pneumonia as the main cause of respiratory distress (68%) with maternal history of PROM >24 hrs as one of the risk factor for it.…”
Section: Discussionmentioning
confidence: 75%